A comparative study of local and foreign packages on the Ghanaian market - Ockumpah-Bortei, Seth Bortequaye (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Arts in Art Education,